Can the ecological transition of cropland use narrow rural-urban income inequality? Evidence from China’s Huang-Huai-Hai Region - Linpeng Yang; Yansui Liu; Cong Ou; Yurui Li (Land Use Policy, 2026)

Advances in halide ion-mediated advanced oxidation processes for high-salinity wastewater treatment: Mechanisms of reactive oxidative species transformation and halogenated by-product formation - Yu Wang; Bing Yang; Yumin Zhang; Lingli Li; Chao Zhu; Yurui Li; Shaoqing Chen; Lili Ma; Mingyan Chen; Yucheng Liu (Chemical Engineering Journal, 2026)

Seasonal hydrology shapes the spatiotemporal distribution of microplastics, antibiotics, ARGs, and sediment bacterial communities in the water-sediment interface - Yurui Zhang; Wei Wang; Xin Meng; Jingyan Hao; Jingru Yang; Simin Li (Journal of Environmental Chemical Engineering, 2026)

Thermodynamically driven oxygen-rich vacancies in La2Ce2O7 boost Ni-catalyzed hydrogen production via steam reforming of plastic pyrolysis gas - Lin Li; Hwanyong Yang; Yurui Wang; Fuhua Xu; Shuang Li; Wei Zhang; Yixiang Shi; Ningsheng Cai (Chemical Engineering Journal, 2026)

Changing characteristics of maize drought in different climate zones of China based on the continuous days without available precipitation - Yue Qi; Heling Wang; Yurui Tang; Yang Yang; Hong Zhao; Funian Zhao; Kai Zhang; Fei Chen; Xingxing Wei; Xiaofeng Yang (Theoretical and Applied Climatology, 2026)

VVFGO: a robust IMU/AHRS/USBL integrated navigation framework with adaptive virtual velocity factor correction for deep-sea docking - Ruiheng Liu; Xinyu Fei; Suohang Zhang; Yurui Zhang; Shipang Qian; Lu Wang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2026)

Research on space object orbit prediction based on a BiLSTM neural network - Qingshan Luo; Ying Cao; Jiahao Ji; Yadi Song; Yurui Xu; Tao Yang (Journal of Space Safety Engineering, 2026)

Revealing the lifecycle evolution of hail-producing deep convective clouds by synergy of multi-source data - Qiang Li; Hongrong Shi; Yurui Xie; Rubin Jiang; Chaoying Wang; Yupeng Teng; Shuo Jia; Jianwei Wen; Disong Fu; Jiefan Yang; Xuehua Fan; Jinqiang Zhang; et al. (Atmospheric Research, 2026)

Isolation of reassortant H5N1 and H5N8 avian influenza viruses from co-infections and their host-dependent replication dynamics - Yuwei Wu; Nuo Xu; Zhifan Li; Zijun Lu; Yurui Dong; Yijie Guo; Ying Bian; Kunlin Li; Chenzhi Huo; Tao Qin; Sujuan Chen; Hui Yang; et al. (Veterinary Microbiology, 2026)

Relationship between lightning channel extension and charge transfer during initial continuous current and continuing current in negative artificially triggered lightning - Jingxuan Wang; Yang Zhang; Yijun Zhang; Yanfeng Fan; Yurui Li (Atmospheric Research, 2026)

Gobi-sourced dust and dust–climate feedbacks in the March 2023 East Asian storm - Shuna Liang; Bin Wang; Yurui Zhang; Junhua Yang; Ove W. Haugvaldstad; Hui Tang (Atmospheric Research, 2026)

A pH/ROS dual-responsive hydrogel enabling a therapeutic trinity of anti-oxidation, anti-inflammation & anti-fibrosis for myocardial infarction repair - Jiao Zhou; Lingbing Zou; Zi Ye; Weiwei Jiang; Jianyu Zheng; Yurui Deng; Linhong Sun; Beibei Guo; Sizhen Wang; Feifei Dong; Feng Yang (Chemical Engineering Journal, 2026)

Heat blocking mechanism and performance evaluation of flame-retardant modified bacterial cellulose aerogel for lithium-ion battery thermal runaway propagation prevention - Xiangming Hu; Zhijun Zhang; Yurui Deng; Zhiyuan Yang; Yajie Luo; Lihua Jiang; Mengdan Zhang; Longfei Han; Yuan Cheng (Chemical Engineering Journal, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

Environmental DNA metabarcoding reveals taxon-specific community divergence between remote atolls and isolated reefs in the South China Sea - Yu Meng; Yurui Yang; Jinping Luo; Jie Yu; Ruiyu Tao; Zhihao Wang; Jiehong Liu; Wentong Xia; Fei Cheng; Songguang Xie; Yiqing Song (Acta Oceanologica Sinica, 2026)

Current status of phylogenetic studies on ciliated protists (Alveolata, Protozoa, Ciliophora) by the OUC-group: advances, challenges and future perspectives - Feng Gao; Yang Bai; Yong Chi; Xiaochen Feng; Chunyu Lian; Borong Lu; Xiaotian Luo; Mingzhen Ma; Congcong Wang; Yurui Wang; Zhe Wang; Gongaote Zhang; et al. (Marine Life Science & Technology, 2025)
Ciliated protists (ciliates) represent a morphologically and genetically diverse group of single-celled eukaryotes, the phylogeny of which is critical for understanding eukaryotic evolution. Through international collaborations, the Laboratory of Protozoology at Ocean University of China (OUC-group) has conducted detailed research on ciliate phylogeny based on expanded taxonomic sampling, employing single gene as well as multi-gene markers, and phylogenomic datasets. We have systematically investigated > 1000 ciliate species spanning ~ 40 orders, sampled from diverse biotopes including marine environments in China seas and freshwater wetlands. This comprehensive sampling has generated three key datasets: (1) genomic DNA extracts from ~ 2600 strains, (2) ~ 2300 sequences of marker genes, and (3) single-cell genomic and/or transcriptomic datasets from ~ 120 species. Based on these datasets, the phylogenetic relationships covering all classes and most orders have been thoroughly reconstructed and investigated, resulting in the establishment of 93 new supraspecies taxa comprising two classes (Mesodiniea and Protocruziea), two subclasses (Protohypotrichia and Synhymenia), two orders (Wilbertomorphida and Lynnellida), 11 families, and 76 genera. Moreover, we have reconstructed a genome-scale tree of life for ciliates and provided an updated classification of the phylum Ciliophora. Furthermore, based on the robust phylogenetic tree of ciliates, we provide more reliable estimates for the origins and divergence times of the main ciliate groups. Future studies integrating advanced genomics, innovations in culturing and interdisciplinary applications will refine the ciliate tree of life, with broader impacts for our understanding of eukaryotic evolution and biodiversity.

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

A vertical docking system based on the autonomous underwater shuttle for seafloor communication relay - Xiaoyan Zhao; Xinyu Fei; Suohang Zhang; Ning Tan; Zhangpeng Tu; Anzhe Yi; Yurui Zhang; Canjun Yang; Yanhu Chen (Ocean Engineering, 2025)

Temperature shapes the global distribution of organic carbon in lake surface sediments - Yongquan Lin; Sheng Yang; Mengting Zhao; Xuerui Lyu; Lingmei Xu; Wengang Kang; Xinwei Yan; Yurui Zhang; Jianbao Liu (Journal of Geographical Sciences, 2025)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

Significantly enhanced piezoelectric properties of BaTiO3-based ceramics with unchanged curie temperature via local chemical inhomogeneity - Ming Wu; Ruifeng Yao; Chengyichang Jin; Yurui Xu; Jingzhe Xu; Liqiang He; Yang Yang; Yongbin Liu; Lisheng Zhong; Jinghui Gao (Chemical Engineering Journal, 2025)

Design of the TP-1B satellite’s laser retro-reflector array and analysis of laser ranging - Qingshan Luo; Xu Liu; Tao Yang; Yurui Xu; Wei Zhu; Yunsheng Yao (Advances in Space Research, 2025)

Preparation of K-carrageenan /polylactic acid nanofiber membranes encapsulating Vitamin C/ Hydroxypropyl-beta-cyclodextrin inclusion complexes by electrostatic spinning for blueberry preservation - Lingling Bai; Yurui Wu; Huijin Xu; Jiyuan Yang; Yiting Lu; Wenge Yang; Yonghong Hu (Food Bioscience, 2025)

Decaying logs and gap positions jointly maintain the structure and function of soil invertebrate community in a subalpine forest - Yurui Jiang; Zhuang Wang; Rui Cao; Qin Wang; Weizhong Li; Wanqin Yang (Plant and Soil, 2025)

Electrostatic spinning construction of GA/HP-β-CD functionalized COS/PLA composite membrane for cherry tomato preservation applications - Wenge Yang; Jiaxing Hao; Yurui Wu; Yuheng Zhou; Li Mi; Yonghong Hu (Food Packaging and Shelf Life, 2025)

The clinical characteristics of Streptococcus equi ssp. zooepidemicus causing acute death in pigs and its prevention with chimeric monoclonal antibodies - Chen Yuan; Yuchang Wang; Xiaowen Zhang; Xingyu Tian; Ying Liang; Fei Pan; Haoshuai Song; Linya Xia; Zhihui Wu; Wenqing Wang; Xiaowen Zhang; Yurui Xie; et al. (Veterinary Microbiology, 2025)

Distribution and ecological risks of microplastics in a tropical tourism island area in Hainan, China - Weijie Bian; Rui Sun; Yurui Li; Shuguo Lü; Dongwei Yang; Hongbo Li; Yingxu Zeng; Min Liu (Journal of Oceanology and Limnology, 2025)

Exploring key aroma differences of three Fenghuang Dancong oolong teas and their perception interactions with caffeine via sensomics approach - Yurui Song; Jingzhe Li; Qiayun Ding; Xiang Yang; Jieyao Yu; Yanyan Zhang; Yijun Wang; Xiaochun Wan; Xiaoting Zhai (Food Research International, 2025)

PCL/soy peptide nanofibers incorporated with riboflavin/HP-β-CD assemblies for improving fruit storage quality - Wenge Yang; Aili Wang; Yurui Wu; Yuheng Zhou; Yonghong Hu (Food Chemistry, 2025)

Unveiling the neglected impacts of halide ions on phenol removal in UV/H2O2 system: Light shielding and oxidant utilization efficiency - Bing Yang; Ying Qiu; Qiuping Luo; Xiangfu Huang; Yurui Li; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Water Process Engineering, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Cumulative effects of cyclic train loading on strains in reinforced soils around tunnels - Jiaofeng Li; Yang Cao; Fasheng Chen; Yurui Lin (Soil Dynamics and Earthquake Engineering, 2024)

Study on cooling efficiency and mechanism of lithium-ion battery thermal runaway inhibition by additives enhanced water mist based on boiling heat transfer theory - Xiangming Hu; Zhiyuan Yang; Yurui Deng; Ming Li; Qingsong Wang; Hongbin Wei; Xiaoxuan Wei; Guoyu Han (Process Safety and Environmental Protection, 2024)

Investigation on the rotary atomization evaporation of high-salinity desulfurization wastewater: Performance and products insights - Yurui Wang; Lingxiao Zhan; Qiwei Luo; Heng Chen; Juecen Mao; Jun Wan; Chaozhen Liu; Haijie Chen; Suoqi Zheng; Zhanxing Chen; Zhihao Li; Linjun Yang (Journal of Environmental Management, 2024)

Characterizing energy-related occupant behavior towards urban residential buildings in China with statistical database establishment - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Yue Chen (Energy and Buildings, 2024)

Advances in modified zero-valent iron materials: Synthesis methods, field studies, practical applications and challenges - Yurui Li; Shijie Zhou; Yuan Meng; Ying Qiu; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu; Bing Yang (Chemical Engineering Journal, 2024)

Thermal stability of PVDF-HFP based gel electrolyte for high performance and safe lithium metal batteries - Xiaoxuan Wei; Yurui Deng; Xiangming Hu; Zhiyuan Yang; Guoyu Han; Hengxu Xu; Zhijun Zhang (Chemical Engineering Journal, 2024)

Unveiling the kinetics and mechanism of sulfide-modified zero-valent iron activated hydrogen peroxide for phenol degradation - Bing Yang; Yurui Li; Yuan Meng; Ying Qiu; Mi Zhou; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Environmental Chemical Engineering, 2024)

High nitrogen application in maize enhances insecticide tolerance of the polyphagous herbivore Spodoptera litura by induction of detoxification enzymes and intensification of cuticle - Jie Wang; Zhihui Lu; Lin Hu; Runbin Zhong; Cuicui Xu; Yurui Yang; Rensen Zeng; Yuanyuan Song; Zhongxiang Sun (Pesticide Biochemistry and Physiology, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Morphology, morphogenesis and molecular phylogeny of a new soil ciliate, Lamtostyla paravitiphila nov. spec. (Ciliophora, Hypotrichia) - Tengteng Zhang; Furui Lu; Xiaoqing Yang; Yurui Wang; Chen Shao (European Journal of Protistology, 2024)

Occurrence states and migration of water during the evaporation of desulfurization wastewater - Lingxiao Zhan; Dawei Hou; Heng Chen; Yurui Wang; Suoqi Zheng; Zhihao Li; Hao Wu; Haijie Chen; Xiaoyue Ma; Linjun Yang (Desalination, 2024)

Orbital modulation of an intensified hydrological cycle during the Paleocene-Eocene Thermal Maximum - Jingyu Zhang; Chunlian Wang; Xiaohua Teng; David B. Kemp; Zhixiang Wang; Hu Yang; Congcong Gai; Yurui Zhang; Yi Zhong; Xiaodong Jiang; Qi Zhang; Weijie Zhang; et al. (Earth and Planetary Science Letters, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Development of a probabilistic agricultural drought forecasting (PADF) framework under climate change - Yizhuo Wen; Yifan Fei; Yurui Fan; Aili Yang; Bingqing Wang; PangPang Gao; Daniel Scott (Agricultural and Forest Meteorology, 2024)

Deep integration of pyrolysis kinetics and pyrolysis mechanism of polyimide aerogels - Xiangming Hu; Hongbin Wei; Yurui Deng; Zhiyuan Yang; Xiaoxuan Wei; Guoyu Han (Fuel, 2024)

A comparative study of accuracy in major adaptive filters for motion artifact removal in sleep apnea tests - Yongrui Chen; Yurui Zheng; Sam Johnson; Richard Wiffen; Bin Yang (Medical & Biological Engineering & Computing, 2024)
Sleep apnea is probably the most common respiratory disorder; respiration and blood oxygen saturation (SpO 2 ) are major concerns in sleep apnea and are also the two main parameters checked by polysomnography (PSG, the gold standard for diagnosing sleep apnea). In this study, we used a simple, non-invasive monitoring system based on photoplethysmography (PPG) to continuously monitor SpO 2 and heart rate (HR) for individuals at home. Various breathing experiments were conducted to investigate the relationship between SpO 2 , HR, and apnea under different conditions, where two techniques (empirical formula and customized formula) for calculating SpO 2 and two methods (resting HR and instantaneous HR) for assessing HR were compared. Various adaptive filters were implemented to compare the effectiveness in removing motion artifacts (MAs) during the tests. This study fills the gap in the literature by comparing the performance of different adaptive filters on estimating SpO 2 and HR during apnea. The results showed that up-down finger motion introduced more MA than left-right motion, and the errors in SpO 2 estimation were increased as the frequency of movement was increased; due to the low sampling frequency features of these tests, the insertion of adaptive filter increased the noise in the data instead of eliminating the MA for SpO 2 estimation; the normal least mean squares (NLMS) filter is more effective in removing MA in HR estimation than other filters. Graphical abstract

Hypoxia Potentiated Lung Cancer Cell Migration and Invasion by up-regulating HIF1α/JAK2/STAT3 Axis and Activating MMP13 Transcription - Xiaoju Cheng; Damin Liang; Xiaoqian Li; Chengmin Deng; Meng Ye; Jiao Yang; Yurui Liu; Kaifeng Wu; Jie Wu; Peng Tian (Cell Biochemistry and Biophysics, 2024)

Study on the evaporation performance of concentrated desulfurization wastewater and its products analysis - Yurui Wang; Lingxiao Zhan; Heng Chen; Juecen Mao; Haijie Chen; Xiaoyue Ma; Linjun Yang (Journal of Water Process Engineering, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Assessing sustainable transformation and development strategies for gully agricultural production: A case study in the Loess Plateau of China - Lulu Qu; Yurui Li; Feng Yang; Li Ma; Zongfeng Chen (Environmental Impact Assessment Review, 2024)

Prediction of urban residential energy consumption intensity in China toward 2060 under regional development scenarios - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Zhiqin Rao; Yue Chen (Sustainable Cities and Society, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Distinguishing anaerobic digestion from electrochemical anaerobic digestion: Metabolic pathways and the role of the microbial community - Nan Wang; Yutong Yang; Kunde Xu; Xiangang Long; Yurui Zhang; Hongzhou Liu; Tiezhu Chen; Jianchang Li (Chemosphere, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

An algal-bacterial symbiotic system of carbon fixation using formate as a carbon source - Yurui Zheng; Jeffrey J. Czajka; Carly Daiek; Zhichang Yang; Liangliang Sun; Yinjie J. Tang; Yan Liu; Wei Liao (Algal Research, 2023)

Stepwise cluster ensemble downscaling for drought projection under climate change - Yizhuo Wen; Aili Yang; Yurui Fan; Bingqing Wang; Daniel Scott (International Journal of Climatology, 2023)
Drought is one of the most serious natural disasters exacerbated by climate change. Changes in precipitation and temperature in the future increase the likelihood of drought in China. In this study, a stepwise cluster ensemble downscaling (SCED) model was developed to bias‐correct projections of temperature and precipitation from multiple RCM outputs, and further characterized the drought hazards. The developed SCED model was used to aggregate and correct the results of multiple regional climate models, and its performance was proved to be reliable by comparing with the observed results. The proposed SCED method has been applied for drought projections over the Fujian province, China. The results showed that the changes of precipitation and temperature in Fujian would have obvious spatial heterogeneous characteristics. The temperature in the southeast coastal areas will increase by up to 4°C and the precipitation will decrease by 3.1% in the late 21st century, while the temperature rises and precipitation increases in the southwest. Temperature in inland areas will be lower and precipitation will be less. The drought hazards were also characterized by both SPI and SPEI based on biased‐corrected projections from SCED model. According to the SPI and SPEI indices, although the number of dry months in Fujian province will not change significantly in future, the spatial and temporal heterogeneity may become more explicit. Moreover, the moderate drought (from SPI) may increase while the general drought may decrease (from both SPI and SPEI). For extreme droughts, there would not be visible changes detected by SPI, but an increasing trend characterized since the impact of temperature was included in SPEI. In addition, there would be an increasing trend on drought when increasing temperature and precipitation occurred simultaneously.

Research on non-contact wet mateable connector for optical communication and power transmission - Zhiyong Duan; Yurui Zhang; Jiaqi Hu; Bohao He; Canjun Yang (Frontiers in Marine Science, 2023)
At present, contact watertight connectors are commonly utilized for the connection between underwater electromechanical equipment and the seabed observation network. Such traditional watertight connectors are easy to be irreversibly worn when plugging and unplugging, however, they have complicated sealing structures and limited service life. This paper designs a Non-contact Wet Mateable connector for Optical Communication and Power Transmission (OCPT-NWMC), which is based on technology of Contactless Power Transmission (CLPT) and optical communication. Docking structure of the sockets and plugs are designed, facilitating Remotely Operated Vehicle (ROV) to operate. A prototype of the OCPT-NWMC was established. The experimental results show that the connector designed can achieve 200W power transmission, with a maximum power transmission efficiency of 94%. The communication bandwidth reaches 18MHz. The OCPT-NWMC can assist the rapid and safe deployment and operation of seabed observation network.

Characteristics and intrinsic influencing factors of log humification depend on wood traits in a subalpine forest - Zhuang Wang; Qin Wang; Bo Tan; Chenhui Chang; Lifeng Wang; Rui Cao; Yurui Jang; Jörg Müller; Wanqin Yang (CATENA, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Cloning and Expression of Sox2 and Sox9 in Embryonic and Gonadal Development of Lutraria sieboldii - Min Lu; Zenghou Xing; Yurui Zhou; Youhou Xu; Huijing Peng; Jie Zou; Solomon Felix Dan; Zhicai She; Pengliang Wang; Jinfeng Liu; Shaomin Qin; Jialin Yang; et al. (Fishes, 2022)
The Sox family plays essential roles as transcription factors in vertebrates; however, little is known about the Sox family in Lutraria sieboldii. L. sieboldii are pleasant to eat with a short growth cycle and have become one of the best bottom-seeded enrichment species in Guang Xi. In this study, Sox2 (named LsSox2) and Sox9 (named LsSox9) from L. sieboldii were cloned, and their expression patterns were analyzed. The length of the LsSox2 gene coding sequence was 1011 bp, encoding 336 amino acids, and LsSox9 was 1449 bp, encoding 482 amino acids. LsSox2 had its highest expression levels in the ovary, which were 356 times those in testis, whereas LsSox9 presented higher expression in testis, which was 6 times more highly expressed than in the ovary. LsSox2 exhibited the highest expression during the morula stage, which was 20 times that of the D-shaped larvae or zygote. LsSox9 exhibited two expression peaks, one at the four-cell stage and the other at the trochophore stage, while the lowest expression was in the zygote. LsSox9 was 73 times more highly expressed in the four-cell stage than in the zygote stage. During gonadal development, LsSox2 presented the highest expression in the mature ovary, which was 756 times more highly expressed than in mature testis. LsSox9 presented higher expression in testis at the emission stage which was 6 times more highly expressed than in the ovary. These results indicate that LsSox2 and LsSox9 may play important roles in embryonic and gonadal development.

Whole Genomic DNA Methylation Profiling of CpG Sites in Promoter Regions of Dorsal Root Ganglion in Diabetic Neuropathic Pain Mice - Wen Chen; Ting Lan; Qingyu Sun; Yurui Zhang; Danmin Shen; Tingting Hu; Jing Liu; Yingzi Chong; Peipei Wang; Qian Li; Weihua Cui; Fei Yang (Journal of Molecular Neuroscience, 2021)

Vegetation Restoration in Response to Climatic and Anthropogenic Changes in the Loess Plateau, China - Lulu Qu; Yunxin Huang; Lingfan Yang; Yurui Li (Chinese Geographical Science, 2020)

Quantifying the vertical distribution pattern of land-use conversion in the loess hilly region of northern Shaanxi Province 1995–2015 - Zhi Cao; Yurui Li; Zhengjia Liu; Lingfan Yang (Journal of Geographical Sciences, 2019)

Progress of research on urban-rural transformation and rural development in China in the past decade and future prospects - Yansui Liu; Hualou Long; Yufu Chen; Jieyong Wang; Yurui Li; Yuheng Li; Yuanyuan Yang; Yang Zhou (Journal of Geographical Sciences, 2016)